202k views
1 vote
Solve for x.
13^x+7= 12^–9x
Write the exact answer using either

1 Answer

6 votes

I suppose the equation should read


13^(x+7)=12^(-9x)

Take the logarithm of both sides; the base of the logarithm doesn't really matter, so I'll make the "natural" choice:


\ln 13^(x+7)=\ln12^(-9x)

Use the exponent property of logarithms:


(x+7)\ln13=-9x\ln12

Solve for
x:


x\ln13+7\ln13=-9x\ln12


x(\ln13+9\ln12)=-7\ln13


x=-(7\ln13)/(\ln13+9\ln12)

Then divide through the numerator and denominator by
\ln13:


x=-\frac7{1+9(\ln12)/(\ln13)}

Use the change of base formula to rewrite


(\ln12)/(\ln13)=\log_(13)12

So we end up with one of many ways of expressing the solution:


\boxed{x=-\frac7{1+9\log_(13)12}}

User Thad
by
5.5k points